Construct Validity of the Patient‐Reported Outcomes Measurement Information System Gastrointestinal Symptom Scales in Systemic Sclerosis12. Issue 11 (November 2014) - Nagaraja, Vivek; Hays, Ron D.; Khanna, Puja P.; Spiegel, Brennan M. R.; Chang, Lin; Melmed, Gil Y.; Bolus, Roger; Khanna, Dinesh
<x xml:space="preserve">Abstract</x> Objective Gastrointestinal (GI) involvement is common in patients with systemic sclerosis (SSc; scleroderma). The Patient‐Reported Outcomes Measurement Information System (PROMIS) GI symptom item bank captures upper and lower GI symptoms (reflux, disrupted swallowing, nausea/vomiting, belly pain, gas/bloating/flatulence, diarrhea, constipation, and fecal incontinence). The objective of this study was to evaluate the construct validity of the PROMIS GI bank in SSc. Methods A total of 167 patients with SSc were administered the PROMIS GI bank and the University of California, Los Angeles, Scleroderma Clinical Trials Consortium Gastrointestinal Scale (GIT 2.0) instrument. GIT 2.0 is a multi‐item instrument that measures SSc‐associated GI symptoms. Product‐moment correlations and a multitrait–multimethod analysis of the PROMIS GI scales with the GIT 2.0 symptom scales were used to evaluate convergent and discriminant validity. Results Patients with SSc GI involvement had PROMIS GI scale scores 0.2–0.7 SD worse than the US general population. Correlations among scales measuring the same domains for the PROMIS GI and GIT 2.0 measures were large, ranging from 0.61 to 0.87 (average r = 0.77). The average correlation between different symptom scales was 0.22, supporting discriminant validity. Conclusion This study provides support for the construct validity of the PROMIS GI scales in SSc. Future research is needed to assess the responsiveness to change of these scales in patients with SSc.